Montaigne’s Scepticism: The Rise of a New Rationalism - Droblytė, Danguolė (Problemos, 1983)
The origin and structure of Montaigne’s method of scepticism which played the role of a peculiar non-gnoseological method of criticism aimed at the medieval world outlook and church dogmatism. The author reveals the transcendental character of Montaigne’s method directed against the attempts of scholastics to ground the religious revelation by rational arguments, as well as against leaving human mind at the service of theology. A conclusion is drawn in the article that Montaigne’s scepticism being based on arguments of natural philosophy has marked the way to scientific cognition and signified the rise of the French philosophical thought in the second half of the 16th century.